2018
DOI: 10.1108/et-07-2017-0098
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence towards entrepreneurial career choice behaviours

Abstract: Purpose The purpose of this paper is to assess emotional intelligence levels and their contributions to entrepreneurial career choice behaviours among Malaysian public university students. Design/methodology/approach This study surveyed 369 respondents selected from a population of 87,503 Malaysian public university students using stratified and simple random sampling techniques. Respondents were given a three-part questionnaire covering their personal information, their emotional intelligence in terms of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 64 publications
3
16
0
2
Order By: Relevance
“…Based on research conducted by Fakhreldin (2017) that emotional intelligence has a significant effect on entrepreneurial intentions. In line with research conducted by Othman et al (2018), someone who is able to manage his emotional intelligence prefers a career as an entrepreneur rather than working as an employee or employee.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Based on research conducted by Fakhreldin (2017) that emotional intelligence has a significant effect on entrepreneurial intentions. In line with research conducted by Othman et al (2018), someone who is able to manage his emotional intelligence prefers a career as an entrepreneur rather than working as an employee or employee.…”
Section: Introductionsupporting
confidence: 63%
“…A family environment that supports and contributes to children to start a business, will provide a positive stimulus to the individual in building his new business, and also develops when it is already running H4. Emotional intelligence has a positive effect terhada interest in entrepreneurship Othman et al (2018) said that with emotional intelligence that is owned by individuals will shape individual behavior in choosing a career for entrepreneurship by managing, understanding and facilitating their thinking using their emotions. In line with research conducted by Fakhreldin (2017) that emotional intelligence has a significant effect on entrepreneurial intentions.…”
Section: H3 Family Environment Positive Effect On the Interest In Enmentioning
confidence: 99%
“…The authors argued that students with knowledge of their own emotions may conduit negative and/or positive affections on the proper identification and resolution of business creation relevant problems. Following this line of thinking, Othman and Muda (2018) also suggested that emotional intelligence is associated with creative and innovative attitudes among students. Individuals with high emotional intelligence are able to generate creative ideas, which eventually shape their entrepreneurial characteristics, ultimately leading to entrepreneurial behaviours (Ngah and Salleh, 2015).…”
Section: Literature Review and Proposed Hypothesismentioning
confidence: 97%
“…Students’ emotional intelligence can help them to develop some entrepreneurial characteristics and possibly to have entrepreneurial behaviour (Hassan and Omar, 2016). Othman and Muda (2018) had analysed the importance of emotional intelligence while managing the moments of difficulty in making the right choices for a future profession. Emotional intelligence may be one of the ways to manage feelings of disappointment and help recover the confidence needed to fight such feelings.…”
Section: Literature Review and Proposed Hypothesismentioning
confidence: 99%
“…Students with knowledge of their emotions can channel negative or positive affections on the identification and resolution of problems relevant to the creation of the right business. The importance of emotional intelligence, because it has a relationship with creative and innovative attitudes among students [24]. Individuals with high emotional intelligence can generate creative ideas, which form entrepreneurial characteristics [25].…”
Section: Partial Testing Shows That Entrepreneurial Learning Towards Entrepreneurial Intentions Is Supported Bymentioning
confidence: 99%